A rare case of recurrent laryngeal hamartoma - Manel Hsairi (Otolaryngology Case Reports, 2021)
Hamartomas are rarely found in the upper respiratory tract and especially in the larynx. Laryngeal hamartomas can cause stridor, eating difficulties and respiratory distress. We report a case of a two-month-old infant who suffered from congenital stridor and was hospitalized for inspiratory dyspnea. The cause was found to be a laryngeal mass and it was surgically removed. The histologic examination later revealed a laryngeal hamartoma. A tracheostomy had to be performed due to the prolonged intubation period. Five months post-surgery, the tumor relapsed and the infant died during biopsy.